2019
DOI: 10.12968/bjca.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Validity and test-retest reliability of a patient-reported outcome measure for an outpatient cardiac rehabilitation programme

Abstract: Background/Aims This article details how a patient-reported outcome measure (PROM), termed PROM-CR1, was tested for acceptability, validity and test-retest reliability at the end of an outpatient cardiac rehabilitation programme. Methods PROM-CR1 was completed by 138 service users (mean age 66.95 years, range 42–94 years; 115 males, 23 females; with a range of cardiac diagnoses), who used the tool at home twice: once at the end of the outpatient cardiac rehabilitation programme and 1 week later. Results PROM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For the study, we will focus on ‘what to measure’. The outcome measures, especially those for patient-reported outcomes, 29 should be searched, assessed and agreed on by different stakeholders according to the guideline on ‘how to select outcome measurement instruments for outcomes included in a COS’. 31 Thus, we plan to conduct a new study to recommend ‘how to measure’ core outcomes, after the final COS is developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the study, we will focus on ‘what to measure’. The outcome measures, especially those for patient-reported outcomes, 29 should be searched, assessed and agreed on by different stakeholders according to the guideline on ‘how to select outcome measurement instruments for outcomes included in a COS’. 31 Thus, we plan to conduct a new study to recommend ‘how to measure’ core outcomes, after the final COS is developed.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes will be presented according to specific interventions and follow-up lengths, because previous research has shown that this approach may improve the adoption of COSs by Chinese trialists. 29 …”
Section: Methodsmentioning
confidence: 99%